A comparative study of chromatic dispersion compensation in 10 Gbps SMF and 40 Gbps OTDM systems using a cascaded Gaussian linear apodized chirped fibre Bragg grating design. Issue 4 (April 2022) - Nsengiyumva, Isidore; Mwangi, Elijah; Kamucha, George
Abstract: Optical time domain multiplexed (OTDM) technology helps to respond to the need for increased capacity and demand in internet traffic using optical transmissions. High-speed optical networks are highly affected by chromatic dispersion (CD) that causes pulse broadening and intersymbol interference (ISI) at the light detector. This paper presents a comparative analysis of chromatic dispersion compensation on 10 Gbps single mode fibre (SMF) and 40 Gbps OTDM operating at C-band using Gaussian apodized linear chirped fibre Bragg grating, Erbium Doped Fibre Amplifier (EDFA) and uniform fibre Bragg grating (UFBG) hybrid approach in OptiSystem 18. A cascade of four UFBG and chirped Bragg gratings design approach presents minimal improvement in the quality factor and achievable single mode fibre length. Quality factor results at a reference wavelength of 1550 nm were obtained for respective chirped Bragg grating lengths of 8 mm, 20 mm, 50 mm, 87 mm, and 90 mm using linear Gaussian apodization. The Q-factor results obtained using the proposed simulation model for single 10 Gb/s channel were respectively 51.14 dBm over 30 km at a grating length of 20 mm and 15.64 dBm over 150 km at 45 mm of grating length. Different eye-diagrams corresponding to varying grating lengths have also been presented for 10 Gb/s and 40 Gb/s at corresponding SMF lengths. Abstract : Chromatic dispersion compensation; Apodized chirped fibre Bragg grating; Optisystem.